IgLON5 autoimmunity in a patient with Creutzfeldt–Jakob disease: case report and review of literature - Li, Xiaofeng; Chen, Yimin; Zhang, Le; Zhang, Wei; Li, Bin; Baizabal-Carvallo, José Fidel; Song, Xingwang (Frontiers in Neurology, 2024)
Objective We present the case of a patient with clinical and imaging features of sporadic Creutzfeldt–Jakob disease (sCJD) and positive IgLON5 antibodies (Abs) in the serum and CSF. Case report A 66-year-old Chinese man presented to the hospital with a stroke-like episode, followed by rapidly progressive cognitive decline, mutism, and parkinsonism. The MRI results showed a cortical ribboning sign in diffusion-weighted MRI, periodic triphasic waves with a slow background in EEG, and positive protein 14–3-3 in CSF. There were matching IgLON5 Abs in the serum and CSF. A literature review showed positive autoimmune encephalitis Abs or autoimmune inflammatory disease between 0.5 and 8.6% among patients with clinical suspicion of CJD, most commonly anti-voltage-gated potassium channel (VGKC) complex and anti-N-methyl-D-aspartate receptor (NMDAR) Abs; however, IgLON5 autoimmunity in CJD has been rarely reported. This is an intriguing association as both conditions have been associated with brain deposits of phosphorylated tau protein. Conclusion IgLON5 Abs may be observed in patients with a diagnosis of CJD; it is unknown whether a synergistic effect of IgLON5 Abs with CJD exists, increasing neurodegenerative changes.